Granger Causality Model of Retained Earnings and Financial Performance of Nonfinancial Firms Listed at the Nairobi Securities Exchange (NSE), Kenya - Akali James Agembe (European Scientific Journal, ESJ, 2024)
Non-financial firms are central to economic development of nations, producing goods and services and alleviating unemployment by creating numerous job opportunities. Despite this potential inherent in non-financial firms, evidence shows that the non-financial firms listed at the Nairobi Securities Exchange (NSE) experience challenges in their financial performance which lowers their capacity to invest. Although retained earnings have been used as a source of funding among listed non-financial firms, there is a paucity of research on the predictive power between retained earnings and financial performance of these firms. Therefore, this research addressed this paucity by modeling Granger causality between retained earnings and financial performance of non-financial firms listed at the NSE. The Wald tests revealed that financial performance of the non-financial firms Granger causes retained earnings, but retained earnings do not Granger cause financial performance. The conclusion drawn from these findings is that financial performance of non-financial firms listed at the NSE allows forecasting of future retained earnings. However, future research should leverage emerging advances like Network Granger causality to determine whether bidirectional Granger causality is viable between the two variables.